Nordic school mathematics revisited – on the introduction and functionality of New Math - Prytz, Johan; Karlberg, Martin (NOMAD Nordic Studies in Mathematics Education, 2016)
We investigate the functionality of New Math in order to nuance and deepen our understanding of the process to introduce New Math in Sweden. Our main material is data and statistics from an intervention study conducted during the preparation of the New Math reform in Sweden. In particular we investigate the claim that New Math material had negative effects on students’ learning. Our conclusion is that the claim is, in most parts, incorrect.